Synthesis and Characterization of TiO2-Chitosan Beads and Its Application as A Degradation Agent of Methylene Blue - Rosdiana, Eka Apriliani; Prasetya, Nor Basid Adiwibawa; Gunawan, Gunawan (Trends in Sciences, 2023)
Dye waste is an environmental problem that has a negative impact on the ecosystem. One way to overcome this is by chemically degrading dyes using photocatalyst materials. TiO2 is one of the photocatalysts that can be synthesized by utilizing microwave radiation which is transferred directly to the material. This method takes a short amount of time so it can be completed in a very short time. TiO2 powder has the disadvantage that it is difficult to separate from the waste solution. TiO2 can be modified into beads by utilizing chitosan to produce TiO2-chitosan beads (TCB). In this research, the synthesis of TiO2 was carried out using microwave, followed by modification with chitosan to produce TCB and then its application in the degradation of methylene blue dye waste at various pH, concentration and contact time variations. Material characterization was carried out by determining the surface area of the material using Brunauer-Emmet-Teller (BET), band gap energy with UV-Vis Diffuse Reflectance Spectrocopy (UV-Vis DRS), crystal phase with X-Ray Diffraction (XRD), and surface morphology with Scanning Electron Microscope (SEM). The results showed that the synthesized TiO2 has anatase crystalline phase with an average crystal size of 18.85 nm and a bandgap energy of 3.16 eV. The TCB surface morphology indicated the successful impregnation of TiO2 on the chitosan. This study showed that the optimum performance of TCB was at pH 11 within 5 min and kinetic analysis results follows 2nd order. HIGHLIGHTS Methylene blue dye waste pollutes the aquatic environment TiO2 as a photocatalyst can degrade methylene blue Chitosan is an abundant natural polymer which has high adsorption ability TiO2-chitosan beads material was synthesized to facilitate the separation of the material from the liquid after photodegradation process GRAPHICAL ABSTRACT